"Obra de arte yo too": Eduardo Mendicutti on soccer, glamour, and the "Beckham effect". Issue 2 (2nd April 2016) - Johnson, P. Louise
ABSTRACT: La Susi en el vestuario blanco (2003) is a fictional chronicle of life in the Real Madrid locker room, a privileged insight into the sanctum sanctorum of the world's richest soccer team. The hiring of Susi as glamour coach ostensibly aims to boost the competitive advantage of the galácticos in foreign as well as local markets (reflecting the reality of the club at the time). In Mendicutti's homoeroticizing gaze, it also serves to uncover the homophobic substrate reportedly still common in male team sports and teases at the anxieties of the players. This article explores the peculiar function of Susi as she sets the comic tone of the work and engages with the varied virilities before her. It examines the notions of "glamour" and "identification" both as tongue-in-cheek team objectives and as phenomena with wider relevance for the way spectators relate to sport and players relate to the world around them.